2000
DOI: 10.1088/0954-3899/26/3/304
|View full text |Cite
|
Sign up to set email alerts
|

The empirical description of the level density parameterain the semi-classical model

Abstract: In this paper a formula based on a statistical model of nuclear reactions is used to describe the dependence of the level density parameter a on the average number of excitons nex . This number was evaluated assuming the 'complexity' k of a compound nucleus as derived from the semi-classical description. The coefficients which appear in the generalized formula for a were estimated by fitting the calculated values of a to its experimental values. The resulting dependence of this parameter on both k and the nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…It is worth pointing out that although the quantity agreement between experimental neutron resonance level density and those calculated from formula (7) (in both calculation variants, with the parameters given in tables 1 and 2) appears to be in the range of one order of magnitude, it is not worse than the results obtained, e.g., in [10][11][12].…”
Section: Discussion Of the Calculation Resultsmentioning
confidence: 56%
“…It is worth pointing out that although the quantity agreement between experimental neutron resonance level density and those calculated from formula (7) (in both calculation variants, with the parameters given in tables 1 and 2) appears to be in the range of one order of magnitude, it is not worse than the results obtained, e.g., in [10][11][12].…”
Section: Discussion Of the Calculation Resultsmentioning
confidence: 56%
“…Sonnentrucker et al (1999) have also found two clouds with different radial velocities observed in the 661 nm diffuse interstellar band. Kaczmarczyk (2000) recently identified two components of the interstellar C 2 bands in the ultraviolet spectra of the star X Per, also corresponding to two gaseous layers with different radial velocities. Cernis (1993) has proposed a model of distribution of the two dust layers, based on his finding that the distance of the Perseus clouds increases with the apparent approach to the Galactic equator.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively simple combinatorial calculations [8,9] allow one to obtain the formulae, which are simple and convenient for calculating the particle-hole state densities. The final results, which are obtained on this basis for level densities ρ, can be improved if energy gaps , resulting from the shell model, are introduced into the equidistant single particle level scheme (as in our previous papers [10][11][12]), although then many more difficulties are encountered. Such a procedure, when used for determining a maximum number k of particles, raised above the Fermi level [10], resulted in the correct reproduction of the form of the dependence of the reduced neutron widths n 0 on the neutron number N in the nucleus [10].…”
Section: Introductionmentioning
confidence: 98%